Kebun Organik Di Masa Adaptasi Kebiasaan Baru Pandemi Covid-19 Dengan Memanfaatkan Sampah Rumah Tangga - Rodesia Mustika Roza; Atria Martina; Hari Kapli; Bernadeta Leni Fibriarti; Wahyu Lestari (Unri Conference Series: Community Engagement, 2021)
The World Health Organization has designated Covid-19 as a pandemic that causes activities outside the home to be restricted. In order to maintain health during the pandemic, many people are starting to choose foodstuffs produced from organic farming. The purpose of this activity is to provide information and motivation to society for reuse household waste with appropriate technology to produce compost. This service activity was carried out in Air Dingin Village, Bukit Raya District, Pekanbaru. The initial stage conveys material about the importance of maintaining health during the pandemic by consuming organic vegetables and fruits grown in their respective yards. Furthermore, the practice of making compost using the direct-use compost method and composting in a composter pot. Composting that reuses household waste has succeeded in opening up insight into the importance of the community's role in personal and environmental health and the public's understanding that a healthy life doesn't have to be expensive. In this activity, the participants showed their enthusiasm and stated that they would practice and share their knowledge with others in making compost to overcome the problem of household waste. This activity is also beneficial to keep the environment clean, healthy and beautiful.